Colorimetric Sensing of Hydrogen Peroxide Using Ionic‐Liquid‐Sensitized Zero‐Valent Copper Nanoparticle (nZVCu). Issue 20 (27th May 2020) - Zarif, Faiza; Khurshid, Shazia; Muhammad, Nawshad; Zahid Qureshi, Muhammad; Shah, Noor S.
Abstract: In this study, a stable ionic liquid (IL) mediated zero‐valent copper nanoparticle (nZVCu), namely IL‐nZVCu, has been evaluated for catalytic properties towards H2 O2 ‐mediated TMB (3, 3', 5, 5'‐tetramethylbenzidine) reaction under normal conditions of temperature and pH. The various analytical techniques like Fourier Transform Infrared Spectroscopy (FT‐IR), UV–Vis diffuse reflectance spectroscopy (UV‐Vis DRS), X‐ray powder diffraction (XRD), scanning electron microscope (SEM), Transmission electron microscopy (TEM) and X‐ray photoelectron spectroscopy (XPS) were used to confirm the structure and nano size of nZVCu. The simple protic IL 1‐hydrogen‐3‐methylimidazolium acetate (HmimOAc) with its cation 1‐methylimidazole and anion acetate was synthesized, characterized, and coated on nZVCu to prepared IL‐nZVCu. As a novel mimic peroxidase, IL‐nZVCu could quickly catalyze the oxidation reaction of specific chromogenic substrate TMB, when H2 O2 acts as an oxidant, followed by a remarkable color change in the solution measured by UV/Vis Spectrophotometry. The enhanced catalytic activity and significant color change were greatly dependent on the catalyst dosage, the volume of IL taken, incubation time, H2 O2 concentration, and TMB concentration. Also, IL‐nZVCu showed no response toward ascorbic acid, cholesterol, dopamine, urea and uric acid. Based on these findings, IL‐nZVCu could be effectively used for visual colorimetric sensing of H2 O2 with a limit of detection (LOD) of 44 μM over the dynamic linear range from 40 μM to 1000 μM concentration. Abstract : Zero‐valent copper nanoparticles were synthesized and characterized using analytical techniques. 1‐hydrogen‐3‐methylimidazolium acetate (Ionic Liquid) was coated on nZVCu to prepared IL‐nZVCu. As a novel mimic peroxidase, IL‐nZVCu could quickly catalyze the oxidation reaction of specific chromogenic substrate TMB (3, 3', 5, 5'‐tetramethylbenzidine), when H2 O2 acts as an oxidant, followed by a remarkable color change in the solution. The enhanced catalytic activity and significant color change were greatly dependent on the catalyst dosage, the volume of IL taken, incubation time, H2 O2 concentration, and TMB concentration.